Racial and gender disparities in the effect of new drug approvals on U.S. cancer mortality - Frank Lichtenberg (Academia Medicine)
Objective: To investigate whether there were racial and gender disparities in the effect of new drug approvals on U.S. cancer mortality since 1990. Study design: We estimate two-way (by cancer site and year (1990–2019)) fixed-effects models of the age-adjusted mortality rate for four race/sex groups: white males, white females, black males, and black females. The main explanatory variables of the models are distributed lags of the number of drugs approved for a cancer site. We control for the current and lagged age-adjusted incidence rate. Principal findings: For all four demographic groups, the age-adjusted mortality rate is significantly inversely related to either the number of drugs approved 0–5 years earlier, the number of drugs approved 6–10 years earlier, or both. The approval of one additional drug for a cancer site reduced the mortality rate of white males and black males by about 2% and 1%, respectively, controlling for lagged incidence. The approval of one additional drug for a cancer site 6–10 years earlier reduced the black female mortality rate by about 1.3–58% as much as it reduced the white female mortality rate (2.2%). Conclusions: Some demographic groups may have had greater access to new cancer drugs than other groups. Some cancer drug innovations for certain sites have been shown to be more effective for some groups than for others. Also, there may be racial differences in rates of usage of some drugs for some cancers due to racial differences in levels of trust of biomedical/drug institutions.